Implementation of Just-in-Time (JIT) Policy in Increasing Production Efficiency of Manufacturing Companies - Suwanda, Suwanda (Journal Arbitrase : Economy, Management and Accounting, 2023)
Just-in-Time is an operational management approach that aims to reduce stock, optimize work flow, and increase production responsibility. This research aims to evaluate and analyze the implementation of Just-in-Time (JIT) policies in increasing production efficiency in industrial environments. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of the Just-in-Time (JIT) policy in increasing production efficiency has had a positive impact. By focusing on demand-based production, inventory reduction, and small-lot production setup, the company managed to increase operational flexibility and reduce waste. The emphasis on quality and continuous improvement provides positive results in continuously improving quality standards and production efficiency. Close collaboration with suppliers has also been proven to help maintain a smooth supply chain. Overall, this research provides empirical support for the effectiveness of implementing JIT as a production management strategy that can improve company performance.